Social and Spatial Aspects of Loneliness: Challenges to Belong and Acquiring a Sense of Home in a Senior Housing Facility in Denmark - Anne Mia Steno (Anthropology & Aging, 2023)
This paper contributes to the literature on loneliness by exploring how loneliness is impacted by a sense of home and experiences and negotiations of belonging. With an ethnographic point of departure in a newly established senior housing facility for older adults experiencing loneliness in Denmark, the paper discusses loneliness as a social and spatial phenomenon that is not static and does not exclusively pertain to the individual. Instead, it is something that is reshaped and (re)negotiated among the residents and their surroundings. This holds promise for welfare professionals to work on alleviating loneliness among older adults at senior housing facilities through working with the arrangements of the social and physical environments. This paper also notes that structures and physical settings that are purportedly supportive can also alienate older adults and hence risk worsening their experiences of loneliness.